A Comparative Study of Copper and Zinc Ion Adsorption on to Activated and Non-activated Date-pits - Fawzi Banat; Sameer Al-Asheh; Deaa Al-Rousan (Adsorption Science & Technology)
Date-pits (an agricultural by-product available commercially) were utilized, with and without activation, as an adsorbent for the removal of Zn 2+ and Cu 2+ ions from aqueous solutions. Activated carbons were prepared from date-pits by carbon dioxide activation at 700°C. The effects of contact time, pH, temperature and the adsorbent concentration on the removal of Zn 2+ and Cu 2+ ions were studied. The Freundlich isotherm model described the equilibrium adsorption data. Non-activated date-pits exhibited higher Zn 2+ and Cu 2+ ion uptake than activated date-pits. The uptake of Cu 2+ ions by both activated and non-activated date-pits was higher than the uptake of Zn 2+ ions. The uptake of both metal ions increased on increasing the pH value of the system from 3.5 to 5.0 as well as on decreasing the temperature from 50°C to 25°C. Adsorption capacities for the non-activated date-pits towards Cu 2+ and Zn 2+ ions as high as 0.15 mmol/g and 0.09 mmol/g, respectively, were observed. This study demonstrated that date-pits without any physical or chemical pretreatment could be used as an effective adsorbent for the treatment of waters containing heavy metal ions such as Zn 2+ and Cu 2+ .